Antimicrobial Properties of Biocompatible Poly (?-Caprolactone) Treated with Plant Extract - Pekdemir, Sibel Selçuk; İnci, Şule; Pekdemir, Mustafa Ersin; Kırbag, Sevda (My University, 2023)
Poly (?-caprolactone) (PCL) was synthesized using ethylene glycol initiator and catalyst accompanied by ring-opening polymerization method. The number average molecular weight (Mn) of the obtained polymer was found to be 4000 gmol-1. In addition, the characteristic signals of PCL were determined with Fourier-transform infrared spectroscopy (FT-IR). Decomposition temperatures were investigated by Thermogravimetric Analysis (TGA) and melting temperatures (Tm) were investigated by Differential Scanning Calorimetry (DSC). Tm of PCL at 57.3 °C was observed. PCL was treated with Rumex patientia L. ethanolic plant extract and its effects on Klebsiella pneumoniae ATCC 700603, Bacillus megaterium DSM32, Staphylococcus aureus ATCC25923, Escherichia coli ATCC25322, and Candida albicans FMC17 microorganisms were examined. It was determined that PCL, which did not show antimicrobial activity, showed antimicrobial activity on some microorganisms after being treated with the plant.
Keywords: FT-IR; Antmicrobial; Crystallinity; Poly ?-caprolactone; Rumex patientia.